Platelet Function and Constituents of Platelet Rich Plasma - Pelletier, M. H.; Malhotra, A.; Brighton, T.; Walsh, W. R.; Lindeman, R. (International Journal of Sports Medicine, 2013)
Platelet Rich Plasma (PRP) therapies require blood to be processed prior to application, however, the full assessment of the output of platelet sequestration devices is lacking. In this study the products of the Autologous Fluid Concentrator (Circle BiologicsTM, Minneapolis, MN) and the Gravitational Platelet Separation System (GPS, Biomet, Warsaw, IN, USA) were evaluated in terms of platelet viability and PRP constituents. The AFC and GPS produced 6.4 (±1.0) ml and 6.3 (±0.4) ml of PRP, with platelet recovery of 46.4% (±14.7%) and 59.8% (±24.2%) producing fold increases of platelets of 4.19 (±1.62) and 5.19 (±1.62), respectively. Fibrinogen concentration was increased above baseline PPP produced with the AFC. pH was lower for both of the processed samples than for whole blood. White Blood Cell count was increased around 5 fold. Functional tests showed preserved viability with both devices. This represents essential knowledge that every treating physician should have before they can confidently administer PRP therapy produced by any method. These are the first published results of platelet function for the GPS system and the first performance results of the AFC system. The PRP produced is classified according to broad classifications as Leukocyte-PRP (L-PRP) for both devices.
Keywords: platelet rich plasma; blood; autologous; therapy; p-selectin; viable